ANALYSIS OF THE CHARACTERISTICS OF PUBLIC TRANSPORTATION MODES TO USERS OF LAND TRANSPORTATION MODES AS CITY TRANSPORTATION WITHIN THE PROVINCE - Kamaluddin Lubis (Buletin Utama Teknik, 2019)
Transportation can be interpreted as an activity to move people or goods from one place to another by means of transportation so that people or goods have higher benefits. In this study, we will discuss the characteristics of transport and perceptions of the characteristics of inter-city transportation modes in the province for the Medan-Berastagi route. This is done to find out the characteristics of transport users in cross surveys, as well as perceptions of the transport users of the transport system. Passenger perceptions of comfort, service, responsibility and facilities on inter-city transportation are dominated by moderate and low ratings, while for perceptions of regularity, load and security are dominated by medium and high ratings. Passenger perceptions of speed are high, there were no respondents who stated low speed while perceptions of costs were low, there were no respondents who stated high costs. Based on the results of research data using the chi square test, in general there are no differences or views on the characteristics of transport due to differences in the characteristics of transport while the difference in perception obtained is based on age and type of work on speed, based on income and the purpose of travel to security and based on level education on service.Keywords: Characteristics, Land Transport, Transportation, Cities and Provinces